Proceedings of the International Conference on Science and Technology (ICST 2018) 2018
DOI: 10.2991/icst-18.2018.60
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening of Ant Plant Myrmecodia rumphii Becc.

Abstract: Ant plant Myrmecodia rumphii Becc. is an epiphytic plant that is widely used by local people as an herbal medicine to treat various diseases such as rheumatic and tumors. Methanol extract of M. rumphii Becc. showed high cytotoxicity against shrimp larvae Arthemia salina Leach and antioxidant potential as indicated by high inhibitory activity against DPPH radicals. In the present paper, we provide for the first time the results of phytochemical screening of ant plant M. rumphii Becc. Powder of M. rumphii Becc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…According to Pasaribu et al (2018), ant nest plants from the genera Hydnophytum and Myrmecodia contain various compounds, making them biologically active. Hydnophytum formicarum Folium contains terpenoids, alkaloids, tannins, glycosides, and saponins, while H. formicarum Cortex contains flavonoids, alkaloids, terpenoids, and glycosides.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Pasaribu et al (2018), ant nest plants from the genera Hydnophytum and Myrmecodia contain various compounds, making them biologically active. Hydnophytum formicarum Folium contains terpenoids, alkaloids, tannins, glycosides, and saponins, while H. formicarum Cortex contains flavonoids, alkaloids, terpenoids, and glycosides.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Phytochemical screening of ant nest plants M. Beccarii, Myrmecodia sp., and Hydnophytum sp. indicates that all three species contain flavonoids, triterpenoids/steroids, and saponins (Mardany et al 2016;Pasaribu et al 2018). Pasaribu et al (2018) found that the ant nest plant Myrmecodia rumphii Becc.…”
Section: Phytochemical Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an ethnopharmacology study from some selected regions in Indonesia, the genus of Myrmecodia has been used as traditional medicine by the community in East Indonesia, especially in Papua, to treat inflammation, muscle pain relief, and strengthen the body's immunity [9]. Rural people in the Papua community use the tuber (hypocotyl) powder of the Myrmecodia plant as a brewed drink like tea with decoction method [10], [11]. In the Papua region, Myrmecodia pendens Merr.…”
Section: Traditional Usesmentioning
confidence: 99%